ddPCR Enhances early diagnosis, treatment, prognosis, and pathogen verification in elderly BSI - Peng, Jiayi; Bai, Huili; Li, Ying; Luo, Huating; Li, Jiajun; Dai, Haifeng; Wang, Hongmei; Meng, Tao; Zhang, Jia; Wang, Zhijian; Chen, Xuanxin; Cheng, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBloodstream infection (BSI) exhibits elevated mortality, particularly among elderly patients manifesting atypical symptoms. Although blood culture (BC) remains the diagnostic gold standard, its limited sensitivity and prolonged turnaround time impede early detection. Droplet digital polymerase chain reaction (ddPCR), a novel pathogen detection method with superior sensitivity and rapid results, demonstrates significant diagnostic and prognostic for BSI. However, heightened sensitivity may increase false positive rates, with elderly patients particularly susceptible to specimen contamination and transient bacteremia.MethodsThis retrospective study employed clinical judgment as the diagnostic reference. Patients were stratified into BSI and non-BSI groups, with data collected on ddPCR and BC results, imaging and laboratory findings, medication response, and discharge outcomes. The diagnostic accuracy and antibiotic guidance efficacy of ddPCR and BC were compared, and the clinical utility of ddPCR was evaluated for prognostic assessment and false positive identification.ResultsThe analysis encompassed 355 episodes from 280 elderly patients with suspected BSI. ddPCR demonstrated significantly higher detection rates compared to BC in BSI group (59.33% versus 20.57%). Combined implementation increased detection to 65.07%. Regardless of clinical judgment (59.61% versus 20.57%) or alternative microbiological tests (90.63% versus 7.14%) served as the reference standards, ddPCR exhibited superior sensitivity to BC. No significant differences emerged in antibiotic adjustment rates or therapeutic efficacy between ddPCR and BC. Elevated microbial species diversity correlated with unfavorable discharge outcomes (P<0.001, OR=2.122). Multiple follow-up ddPCR monitoring revealed progressive increases in the number of species and the copies of some (or all) species among patients with poor outcomes, contrasting with decreasing trends in those with favorable outcomes. When detecting Streptococcus, coagulase-negative Staphylococci (CoNS), Acinetobacter baumannii complex, and Candida, diagnostic thresholds of 132.55, 182.70/262.24, and 174.78 copies/mL, respectively, were established to help differentiate false-positive results.ConclusionThe combination of ddPCR with BC improves BSI diagnosis in elderly patients and facilitates antibiotic treatment optimization. Moreover, ddPCR demonstrates potential for prognostic evaluation and false-positive discrimination. Nevertheless, these findings require further validation through large-scale prospective studies employing predefined clinical criteria.